Risk, return, and regulation: how venture capitalists navigate the life sciences sector - Takala, Matias (My University, 2025)
The life sciences sector combines scientific research and technological innovation with the goal of improving human health. While the industry offers high growth potential, it also poses major challenges for investors due to strict regulation, long development cycles, and high capital intensity. Venture capital (VC) has become a critical source of funding for early-stage companies seeking to commercialize scientific innovation in areas such as drug development, medical devices, and digital health. This thesis explores how venture capital investors operate in the complex life sciences sector and identifies the key factors that drive their success. The research aims to identify the factors that distinguish life sciences investing from traditional VC industries and to examine the key challenges and success factors shaping investor performance. The study focuses on differences between life sciences-focused VC funds and generalist VC funds, investigating both the regulatory and market-related dynamics that influence investment decisions. Methodologically, the thesis combines a literature review with an expert interview to integrate theoretical insights with practical perspectives. The literature review draws primarily on U.S. sources, reflecting the leading global market for venture capital and startup activity, while the interview provides first-hand knowledge from an experienced life sciences executive and investor, primarily focusing on the Northern European market. The findings show that successful venture capital investing in the life sciences sector depends on strong professional networks and deep scientific understanding. Investors must be able to accurately evaluate the scientific as well as commercial potential and manage high levels of uncertainty. Precision, scientific thoroughness, and strategic collaboration are fundamental. Investors often adopt a partnership-oriented approach, leveraging shared expertise and networks to identify opportunities and achieve successful exits. Overall, the study emphasizes that networks, scientific understanding, and close collaboration with co-investors are essential for managing the risks of life sciences investing and achieving sustainable returns.

Life science -ala yhdistää tieteellisen tutkimuksen ja teknologisen innovaation ihmisten terveyden edistämiseksi. Ala tarjoaa suurta kasvupotentiaalia, mutta sijoittajille se on haastava tiukan sääntelyn, pitkien kehityssyklien ja korkean pääomaintensiteetin vuoksi. Venture capital (VC) -sijoittaminen on keskeinen rahoitusmuoto varhaisen vaiheen yrityksille, jotka pyrkivät kaupallistamaan tieteellisiä innovaatioita esimerkiksi lääkekehityksen, lääkinnällisten laitteiden ja digitaalisen terveyden aloilla. Tämä tutkielma tarkastelee, miten venture capital -sijoittajat toimivat monimutkaisella life science -sektorilla ja tunnistaa keskeiset ajurit, jotka edistävät heidän menestystään. Tutkimuksen tavoitteena on tunnistaa tekijät, jotka erottavat life science -alan sijoittamisen yleisestä VC-sijoittamisesta, sekä selvittää alan keskeiset haasteet ja menestystekijät, jotka vaikuttavat sijoittajien suoriutumiseen. Tutkimus keskittyy life science -alan VC-rahastojen ja yleisten VC-rahastojen eroihin sekä siihen, miten alan sääntely- ja markkinadynamiikat vaikuttavat sijoituspäätöksiin. Tutkimusmenetelmänä on kirjallisuuskatsaus ja asiantuntijahaastattelu. Tutkielmassa teoreettiset näkemykset yhdistyvät käytännön kokemuksiin sijoittamisesta life science -sektorilla. Kirjallisuuskatsaus pohjautuu pääosin aineistoihin Yhdysvaltojen markkinoilta, jotka edustavat johtavaa globaalia VC-sijoittamisen ja startup-toiminnan kenttää, kun taas haastattelu tarjoaa Pohjois-Euroopan markkinoille painottuvaa ensikäden tietoa kokeneelta life science -alan johtajalta ja sijoittajalta. Tulokset osoittavat, että menestyksekäs venture capital -sijoittaminen life science -alalla perustuu vahvoihin verkostoihin ja syvälliseen tieteelliseen ymmärrykseen. Sijoittajien on pystyttävä arvioimaan tieteellistä ja kaupallista potentiaalia tarkasti sekä hallitsemaan suurta epävarmuutta. Huolellisuus, tieteellinen perusteellisuus ja strateginen yhteistyö ovat alalla keskeisiä. Sijoittajat omaksuvat usein kumppanuuslähtöisen lähestymistavan, jossa jaettua asiantuntemusta ja verkostoja hyödynnetään sijoitusmahdollisuuksien tunnistamisessa sekä onnistuneiden exitien varmistamisessa. Kokonaisuudessaan tutkimus korostaa, että vahvat verkostot, tieteellinen ymmärrys ja tiivis yhteistyö ovat ratkaisevia life science -sijoittamisen riskien hallinnassa ja kestävien tuottojen saavuttamisessa.
Keywords: venture capital, life sciences, biotechnology, drug development, startup, medical devices, riskipääoma, lääkekehitys, lääkinnälliset laitteet, startup-yritys, bioteknologia, venture capital